Utilization and Survival of Postoperative Radiation or Chemoradiation for pT1‐2N1M0 Head and Neck Cancer. (19th December 2017) - Lee, Anna; Givi, Babak; Roden, Dylan F.; Tam, Moses M.; Wu, S. Peter; Gerber, Naamit K.; Hu, Kenneth S.; Schreiber, David
Abstract : Objective: To analyze the patterns of care and survival for pT1‐2N1M0 head and neck cancer based on receipt of surgery alone, surgery + postoperative radiotherapy (S + RT), or surgery + postoperative chemoradiotherapy (S + CRT). Study Design: Retrospective analysis. Setting: National Cancer Database. Subjects and Methods: We queried the database for patients with stage pT1‐2N1M0 squamous cell carcinoma of the oral cavity, oropharynx, hypopharynx, or larynx between 2004 and 2012 who were treated with surgery with negative margins and no extracapsular extension. Logistic regression was used to assess predictors of receipt of postoperative treatment. Overall survival was assessed by the Kaplan‐Meier method, and Cox regression analysis identified covariates that affected it. Results: There were 1598 patients included in this study: 566 (35.4%) received surgery alone; 726 (45.4%), S + RT; and 306 (19.1%), S + CRT. The 5‐year overall survival was 68.8%, 74.0%, and 87.8%, respectively ( P =. 009 comparing S + RT and surgery alone, P <. 001 for all other comparisons). On multivariable logistic regression, academic centers were associated with a decreased likelihood of S + RT (odds ratio = 0.71) and S + CRT (odds ratio = 0.66). Multivariable Cox regression demonstrated no difference in survival for S + RT over surgery alone (hazard ratio = 0.88, 95% CI = 0.70‐1.09, P =. 24); however, there was a survival benefit associated with S + CRT (hazard ratio = 0.57, 95% CI = 0.39‐0.81, P =. 002). Conclusion: Nearly 65% of patients with pT1‐2N1 head and neck cancer with negative margins and no extracapsular extension received S + RT or S + CRT. Improvement in survival was noted only for patients who received S + CRT.